Cohort study into the neural correlates of postoperative delirium: the role of connectivity and slow-wave activity. (July 2020) - Tanabe, Sean; Mohanty, Rosaleena; Lindroth, Heidi; Casey, Cameron; Ballweg, Tyler; Farahbakhsh, Zahra; Krause, Bryan; Prabhakaran, Vivek; Banks, Matthew I.; Sanders, Robert D.
Abstract: Background: Delirium frequently affects older patients, increasing morbidity and mortality; however, the pathogenesis is poorly understood. Herein, we tested the cognitive disintegration model, which proposes that a breakdown in frontoparietal connectivity, provoked by increased slow-wave activity (SWA), causes delirium. Methods: We recruited 70 surgical patients to have preoperative and postoperative cognitive testing, EEG, blood biomarkers, and preoperative MRI. To provide evidence for causality, any putative mechanism had to differentiate on the diagnosis of delirium; change proportionally to delirium severity; and correlate with a known precipitant for delirium, inflammation. Analyses were adjusted for multiple corrections (MCs) where appropriate. Results: In the preoperative period, subjects who subsequently incurred postoperative delirium had higher alpha power, increased alpha band connectivity (MC P <0.05), but impaired structural connectivity (increased radial diffusivity; MC P <0.05) on diffusion tensor imaging. These connectivity effects were correlated ( r 2 =0.491; P =0.0012). Postoperatively, local SWA over frontal cortex was insufficient to cause delirium. Rather, delirium was associated with increased SWA involving occipitoparietal and frontal cortex, with an accompanying breakdown in functional connectivity. Changes in connectivity correlated with SWA ( r 2 =0.257; P <0.0001), delirium severity rating ( r 2 =0.195; P <0.001), interleukin 10 ( r 2 =0.152; P =0.008), and monocyte chemoattractant protein 1 ( r 2 =0.253; P <0.001). Conclusions: Whilst frontal SWA occurs in all postoperative patients, delirium results when SWA progresses to involve posterior brain regions, with an associated reduction in connectivity in most subjects. Modifying SWA and connectivity may offer a novel therapeutic approach for delirium. Clinical trial registration: NCT03124303, NCT02926417